PARENTAL KNOWLEDGE AND DEVELOPMENT OF LANGUAGES AND LITERACY, COMMUNICATION AND SOCIALIZATIONS IN THE EARLY CHILDHOOD EDUCATION - Mohd Sainain, Nik Salmi Nurulhuda; Omar, Romarzila; Ismail, Hazhari; Mamat, Nordin; Abdullah, Ruslan (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to identify the level of parental knowledge of early childhood language development, communication and socialization at the GENIUS National Children’s Center in Alor Gajah district, Malacca. A total of 113 parents at the Alor Gajah GENIUS Children’s Center were involved as a sample of this study. A five-point Likert scale questionnaire was used as the instrument of this study. The questionnaire is based on the developmental items from the GENIUS national curriculum which is language literacy, early communication and literacy socialization. The results of this study were analyzed using Statistical Package for Social Science (SPSS) version 23 software to obtain mean, standard deviation, percentage, t-test and ANOVA test were performed to answer the research hypothesis. The findings showed that (1) parental knowledge of literacy development was moderate (min = 2.85, sp = 0.35), (2) parental knowledge for level of literacy socialization was moderate (min = 2.92 , sp = 0.27), (3) the level of parental knowledge of early childhood communication language and literacy by gender, there was no significant difference in male and female scores (t = 0.574; df = 111, p = 0.25 that> 0.05), (4) the level of parental knowledge of early childhood language and literacy socialization by gender, there were significant differences in male and female scores (t = −1.725; df = 88.809, p = 0.00; <0.05), (5) parental knowledge level in early childhood literacy development by education level, there was no significant difference at p = 0.164, f (3,109) = 1.737, p> 0.05 and (6) knowledge level parental development of early childhood language and literacy socialization by education level, there was no significant difference at p = 0.670, f (3,109) = 0.518, p> 0.05. This shows that parents are knowledgeable about children’s development, especially communication and literacy socialization, which could be seen through parent-child communication and participation in children’s activities. The results show that there is a significant difference in parental knowledge of early childhood language and literacy socialization in the GENIUS National Children’s Center. ,